'The forest belongs to those who work it!': multifaceted dispossession, relations of production, and ethnicity within processes of indigenous autonomy in Cherán, Mexico. Issue 2 (3rd April 2021) - Navarrete, Edgars Martínez
ABSTRACT: This article examines how the process of indigenous autonomy that began in Cherán (in the Mexican state of Michoacán) on 15 April 2011 managed to reverse the regime of violence and dispossession to which the town had been subjected as a result of the incursions of organized crime. We propose to understand this situation as a contemporary expression of multifaceted dispossession organized in pursuit of natural resources found in the forests of the Purhépecha Plateau through the historical deployment of diverse appropriation mechanisms by government and capitalist entities operating throughout the area – dynamics which have fragmented communal production logic and ethnic frameworks in Cherán and other surrounding communities. From our perspective, the antagonistic nature of this autonomy experience in the face of such power structures and their long-standing modalities lies in the possibility to mobilize economic and political initiatives – insubordinate to capitalism – through the organization of communal relations of production, the promotion of communitarian labor, and the creation of use values with the objective of satisfying common necessities.